Robust stabilization of discrete linear repetitive processes with switched dynamics - Bochniak, Jacek; Gałkowski, Krzysztof; Rogers, Eric; Kummert, Anton (Zielona Góra: Uniwersytet Zielonogórski)
Repetitive processes constitute a distinct class of 2D systems, i.e., systems characterized by information propagation in two independent directions, which are interesting in both theory and applications.
Keywords: repetitive processes; 2D systems; switched dynamics; stabilization; uncertainty